Toilet dan Proses Inkulturasi Masyarakat Jawa Menjadi Masyarakat Kolonial di Surakarta Abad XX - Muhammad Misbahuddin; Agus Setyawan; Niila Khoiru Amaliya; Rizki Amalia Sholihah (JUSPI (Jurnal Sejarah Peradaban Islam), 2021)
This article aims to explain the history of the inculturation process of clean culture through toilets in the twentieth century Surakarta society. The methodology used in this research is historical method using critical historical approach. Using this method, the authors analyze the process of using toilet in a holistic manner, the toilet that is not affected by the socio-political practices. The phenomena are analyzed by using the theory of hegemony Gramsci and the theory of inculturation. The result of this research is that the emergence of the concept of toilet brings a change in the standard of healthy life among the Javanese people. It bears new cultural values, e.g. the value of modesty and embarrassment that have not recognized by the Javanese people before. It also promotes the concept of privacy body that makes the birth of social stratification.